EVALUATION OF VO2Max ATLET KARATE IN THE COVID-19 PANDEMIC ERA - Suprianto Kadir (Universitas Negeri Gorontalo, 2020)
The research article analyzes the VO2Max level of Karate athletes. The purpose of this study was to determine the impact of independent training carried out by athletes due to the covid-19 pandemic on the athlete's physical status. The method used in this research is a quantitative descriptive method which is conducted as a total sampling of the Gorontalo Province PPLP Karate athletes in the January-December 2020 period of 6 female athletes and 7 male athletes. The findings of the study prove that there was a decrease in the average VO2Max of female athletes by 23% and male athletes by 18%. The application of various forms of training at this stage should be carried out under strict control by the trainer, so that the athlete in carrying out the training program is truly monitored directly and each athlete is serious in carrying it out.